Oscillation Theorems for Even Order Damped Equations with Distributed Deviating Arguments - Chunxia Gao; Peiguang Wang (Abstract and Applied Analysis)
A class of even order damped differential equations with distributed deviating arguments are investigated. Several new criteria that ensure the oscillation of solutions are obtained. To demonstrate the validity of the results obtained, two examples are given.